Komunitas serangga yang berasosiasi dengan buah Ficus racemosa L. - Jauharlina Jauharlina; Afriyani Afriyani; M. Ikram Taufik (Jurnal Entomologi Indonesia, 2017)
Pollination within syconium (figs) of the fig trees (Ficus spp.)  depends on female fig wasps that belong to Family Agaonidae (Order Hymenoptera); on the other hand, the female wasps can only lay eggs inside the fig flowers in which the offspring later develop. Several species of non-pollinating wasps are also known to develop within the figs. A research to investigate the fig wasps community (pollinator and non-pollinator) and their impact on the figs has been conducted on fig tree species of Ficus racemosa L. in Aceh Province. Fig fruits of  F. racemosa were sampled when they were on receptive stage (B-phase) and when the figs were almost mature (D-phase) on the same trees. The young figs were dissected to observe the pollinating wasps (foundresses), while the mature figs were incubated until the new generation of fig wasps emerged from the figs. The wasps then were identified and counted. Observations on B-phase figs showed that the pollinating wasps of F. racemosa was Ceratosolen fuscicep (Mayr) (Hymenoptera: Agaonidae) which entered the fig through ostiole. The fig wasps community that emerged from D-phase figs consisted of pollinating and non-pollinating fig wasps, Platyneura fusca dan P. agraensis (Hymenoptera: Agaonidaed) were the competitors of pollinating wasps in taking the ovules for their development, while Apocrypta sp. (Hymenoptera: Pteromalidae) was a parasitoid of the pollinator. However, in this research there was no evident that the presence of these non-pollinating wasps significantlyt affect the number of pollinating wasps and seeds of F. racemosa.